Faktor Pendukung Dan Faktor Penghambat Keberhasilan Menghafal Al-Qur’an Di Pondok Pesantren Sulaimaniyyah - Abbas Wahid Rifki; Fadina Rahmadiani; Fahmi Syahrul Romadhon; Muhamad Isro'i Ma'ruf; Samrotul Mawaddah; Siti Fathonatul Ula; Triani Okasya (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
The purpose of this study was to analyze the supporting factors and inhibiting factors for the successful process of memorizing the Qur'an at the Sulaimaniyyah Islamic Boarding School in a short time. This research is expected to provide an overview that supports and hinders the process of memorizing the Qur'an at the Sulaimaniyyah Islamic Boarding School and provides recommendations for memorizing methods to other Islamic boarding schools. The research method used is descriptive qualitative research. In collecting data using in-depth interviews and documentation, using data reduction analysis, data presentation and verification. This study also checked the validity of the data by using data source triangulation techniques. The results of the study revealed that there were supporting and inhibiting factors in the process of memorizing the Koran at the Sulaimaniyyah Islamic Boarding School. The supporting factors include adab towards the Qur'an, the obligatory pre-tahfidz program, night prayers or tahajjud, the method used and istikamah murojaah. And the inhibiting factors include smoking, eating food carelessly, using electronic media/cell phones and not istikamah murojaah or repeating memorization.